Cooperative drought adaptation: Integrating infrastructure development, conservation, and water transfers into adaptive policy pathways. Issue 9 (24th September 2016) - Zeff, Harrison B.; Herman, Jonathan D.; Reed, Patrick M.; Characklis, Gregory W.
Abstract: A considerable fraction of urban water supply capacity serves primarily as a hedge against drought. Water utilities can reduce their dependence on firm capacity and forestall the development of new supplies using short‐term drought management actions, such as conservation and transfers. Nevertheless, new supplies will often be needed, especially as demands rise due to population growth and economic development. Planning decisions regarding when and how to integrate new supply projects are fundamentally shaped by the way in which short‐term adaptive drought management strategies are employed. To date, the challenges posed by long‐term infrastructure sequencing and adaptive short‐term drought management are treated independently, neglecting important feedbacks between planning and management actions. This work contributes a risk‐based framework that uses continuously updating risk‐of‐failure (ROF) triggers to capture the feedbacks between short‐term drought management actions (e.g., conservation and water transfers) and the selection and sequencing of a set of regional supply infrastructure options over the long term. Probabilistic regional water supply pathways are discovered for four water utilities in the "Research Triangle" region of North Carolina. Furthermore, this study distinguishes the status‐quo planning path of independent action (encompassing utility‐specific conservation and new supply infrastructure only) from two cooperative formulations: "weak" cooperation, which combines utility‐specific conservation and infrastructure development with regional transfers, and "strong" cooperation, which also includes jointly developed regional infrastructure to support transfers. Results suggest that strong cooperation aids utilities in meeting their individual objectives at substantially lower costs and with less overall development. These benefits demonstrate how an adaptive, rule‐based decision framework can coordinate integrated solutions that would not be identified using more traditional optimization methods. Key Points: Capturing feedback between infrastructure sequencing and short‐term management methods in an optimization framework Risk‐based decision triggers provide a quantitative basis for adaptation to uncertainty that evolve with new information over time Increasing levels of cooperation enables regional actors to meet objectives at lower costs and lower overall development